Life and research trajectories. Devoted to the 70th anniversary of V. P. Kryuchkov - Bochkareva, Tatiana A.; Koshcheeva, Olga V. (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
The paper is dedicated to the anniversary of the famous philologist, literary scholar, methodologist, high school teacher, head of the Department of Speech Therapy and Psycholinguistics of Saratov State University, Vladimir Petrovich Kryuchkov. The relevance of the research is due to the necessity to provide a comprehensive review of the researcher’s scientifi c achievements and works in the fi eld of literary studies, pedagogy, speech therapy, and to understand their role in shaping the content and scientifi c foundations of professional training methods. The purpose of the research is to study the main stages in the development of V. P. Kryuchkov’s professional activity, to make a review of the researcher’s scientifi c and methodological works, to analyze the specifi cs of his interdisciplinary approach to the content of teaching methods which are aimed at professional training of speech therapists in higher education. Methods (tools): analysis of scientifi c and bibliographic sources, including dissertations, monographs, articles, programs and educational materials of the researcher, as well as conference proceedings. Results. The study identifi es the main directions of the scientifi c research, methodological, and teaching activity of the scientist, touches upon their infl uence on the subject-matter of the methods used in professional teacher-training of speech therapists and on the development of the idiosyncrasy of the Department of Speech Therapy and Psycholinguistics of Saratov State University, headed by V. P. Kryuchkov. Practical significance: the results of the research contribute to understanding the sphere of scientifi c interests of V. P. Kryuchkov, his contribution to literary, pedagogical, and special (defectological) areas of humanitarian knowledge, to the development of the training methods content and the interdisciplinary approach in the system of higher education.